Acute caffeine intake increases performance in the 15‐s Wingate test during the menstrual cycle - Lara, Beatriz (Br J Clin Pharmacol, 2020)
AIMS: In male athletes, caffeine is considered an ergogenic aid to increase anaerobic performance during the Wingate anaerobic test (WANT). However, information about the effect of caffeine on WANT performance in female athletes is contradictory. Furthermore, it is unknown whether the ergogenicity of caffeine is present during all the phases of the menstrual cycle. The aim of this study was to investigate the effects of caffeine intake on WANT performance during 3 phases of the menstrual cycle. METHODS: Thirteen well‐trained eumenorrhoeic triathletes participated in a double‐blind, placebo‐controlled, cross‐over experimental trial. On 2 different days in each phase, and in randomized order, participants ingested caffeine (3 mg kg(−1)) or a placebo (cellulose). The menstrual cycle phases were individually characterized as follows: (i) early follicular; (ii) preovulatory; and (iii) midluteal. In each trial, participants performed a 15‐s adapted version of the WANT. RESULTS: In comparison to the placebo, caffeine increased peak power during the WANT in the early follicular (8.6 ± 0.8 vs 8.9 ± 0.9 W/kg, P = .04; effect size [d] = 0.45), preovulatory (8.6 ± 0.9 vs 8.9 ± 0.9 W/kg, P = .04; d = 0.23) and mid‐luteal phases (8.6 ± 0.8 vs 8.9 ± 0.9 W/kg, P < .01; d = 0.52). CONCLUSION: The ergogenic effect of caffeine on WANT peak cycling power was of a similar magnitude in the follicular, preovulatory, and mid‐luteal phases. These results suggest that caffeine increases performance in the 15‐s Wingate test in women athletes and it might be considered an ergogenic aid to increase anaerobic performance in eumenorrhoeic women during their menstrual cycle.